The man - Mundine, Anthony, 1975-; Lane, Daniel (Daniel Q.) (Sydney : Pan Macmillan, 2000)
"Anthony Mundine is young, black and an extraordinarily talented athlete, and when he walked away from rugby league and a $600,000-a year spot with St George Illawarra to become a professional boxer, he created one of the biggest media storms of 2000. In The Man, he tells the real story behind his flight and resignation. But Mundine is more than a sportsman. He's also a highly controversial and outspoken crusader for Aboriginal rights, believing that confrontation is the way to improve conditions for indigenous Australians." - back cover.
Keywords: Mundine, Anthony, -- 1975-; Aboriginal Australian Rugby League football players -- Biography; Rugby League football players -- Australia -- Biography; Rugby League football -- Australia; Sport - Football - Rugby league; History - Biographies - Indigenous - Autobiographies; Child welfare - Child / parent separation - Stolen generations; Sport - Boxing; Law enforcement - Police-youth relations